PENGARUH VARIASI PROPORSI SARI BIT MERAH DAN SUSU UHT TERHADAP SIFAT FISIKOKIMIA, MIKROBIOLOGIS DAN SENSORIS YOGHURT - Susanto, Yanny; Nugerahani, Ira; Kusumawati, Netty (Jurnal Teknologi Pangan dan Gizi, 2014)
Yoghurt is a fermented milk product with activity of Lactic Acid Bacteria (LAB), Streptococcus thermophilus (ST) and Lactobacillus bulgaricus (LB). Red beet juice has attractive purplish red color which is a betalain pigment so it can be an alternative natural dyes for yoghurt products. The purpose of this research is to determine the effect of variation proportion of red beet juice and UHT milk on the physicochemical, microbiological and sensory properties of yoghurt. The experimental design used Randomized Block Design (RBD) with one factor namely proportion of red beet juice and UHT milk which consists of 6 treatments is 0%: 100%, 2%: 98%, 4%: 96%, 6%: 94%, 8%: 92% and 10%: 90% with four replications for each treatment. The parameters observed are acidity, pH, syneresis, total LAB and sensory (preferences of color, aroma and taste). The results of this study showed that the variation proportion of red beet juice and UHT milk affected the physicochemical, microbiological and sensory properties of yoghurt. Increased proportion of red beet juice reduced pH of yoghurt meanwhile acidity, syneresis and total lactic acid bacteria in yoghurt produced increased. The results of weighting test showed that best treatment of red beet yoghurt is 6% red beet juice and 94% UHT milk with a pH value of 4,53, total acid 1,18%, syneresis 0,08%, total LAB 10,5212 log cfu/mL, preference consumer for color 7,29 (like), aroma 7,80 (like) and flavor 7,99 (like).